PERAN ORANG TUA DALAM PEMBERIAN MAKANAN BERGIZI SEIMBANG PADA ANAK USIA DINI - Cholana, Hozania Bellandira; Miranda, Dian; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the role of parents in providing balanced nutritious food to early childhood at Insani Kindergarten, Nanga Taman District. The research method used is descriptive qualitative. The data sources in this study were parents of children who attended Insani Kindergarten, Nanga Taman District and the data collection techniques used were observation, interviews and documentation. The results showed that: 1) The role of parents as mentors in providing balanced nutrition to early childhood in human kindergartens in Nanga Taman District, has been partially implemented by inviting children to adopt a healthy lifestyle such as teaching children to always wash their hands before and after eating, getting children used to to drink water regularly and consume foods that contain balanced nutrition with rice, vegetables, side dishes and fruit in the child's diet, pay attention to the cleanliness of cutlery and help regulate eating patterns. 2) The role of parents as a motivator in providing balanced nutrition to early childhood in human kindergarten in Nanga Taman District, has been partly implemented with the appreciation given by parents to children regarding healthy food, preparation of a varied food menu, creating food supplies and giving freedom children in selecting food menus. 3) The role of parents as facilitators in providing balanced nutrition to early childhood in Insani Kindergarten, Nanga Taman District, has been partially implemented with parents providing adequate nutrition through a complete food menu with balanced nutritional content, both at home and at school.